2017
DOI: 10.1116/1.4993996
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer etching of gallium nitride (0001)

Abstract: In this work, atomic layer etching (ALE) of thin film Ga-polar GaN(0001) is reported in detail using sequential surface modification by Cl2 adsorption and removal of the modified surface layer by low energy Ar plasma exposure in a standard reactive ion etching system. The feasibility and reproducibility of the process are demonstrated by patterning GaN(0001) films by the ALE process using photoresist as an etch mask. The demonstrated ALE is deemed to be useful for the fabrication of nanoscale structures and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…6 Thermal ALE relies on temperature and thermochemically favourable reactions to remove surface species. 10 While there have been many examples of thermal ALE of a range of materials, including: HfO 2 , 4,9,11,12 ZrO 2 , 4,12 SiO 2 , 13 , Al 2 O 3 , 12,[14][15][16][17][18] AlN, 19 AlF 3 , 20 TiO 2 , 21 TiN, 22,23 W, 24,25 WO 3 , 25 ZnO 26 and GaN 27 and for other ALE techniques including Ar neutral beam ZrO 2 , 28 plasma ALE SiO 2 , 29,30 ZnO, 31 GaN 32,33 and ALE of Si 3 N 4 34 using infrared annealing, the details of the mechanism of the ALE process still require significant work to understand. The first step in ALE is the formation of a reactive but non-volatile layer on the initial film, which is followed by a material removal step to take off only the modified layer as indicated schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…6 Thermal ALE relies on temperature and thermochemically favourable reactions to remove surface species. 10 While there have been many examples of thermal ALE of a range of materials, including: HfO 2 , 4,9,11,12 ZrO 2 , 4,12 SiO 2 , 13 , Al 2 O 3 , 12,[14][15][16][17][18] AlN, 19 AlF 3 , 20 TiO 2 , 21 TiN, 22,23 W, 24,25 WO 3 , 25 ZnO 26 and GaN 27 and for other ALE techniques including Ar neutral beam ZrO 2 , 28 plasma ALE SiO 2 , 29,30 ZnO, 31 GaN 32,33 and ALE of Si 3 N 4 34 using infrared annealing, the details of the mechanism of the ALE process still require significant work to understand. The first step in ALE is the formation of a reactive but non-volatile layer on the initial film, which is followed by a material removal step to take off only the modified layer as indicated schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…For Ar activation, the EPC at the ALE window is in good agreement with values in the 0.37-0.42 nm/cycle reported in the literature for ALE of GaN with Ar ion activation. 14,15 For energies below the lower limit of the ALE window, −16 V and −15 V, respectively, removal of the modified layer is assumed to be inexistent or incomplete due to insufficient energy for the incoming ions. For energies above the upper limit, −22 V and −17 V, respectively, sputtering of bulk materials occurs without any self-limitation once the removal of the modified layer is completed.…”
Section: E Discussionmentioning
confidence: 99%
“…ALE is under development nowadays to achieve atomic-scale control for nanoscale device fabrication for various materials including semiconductors, metals, and dielectrics; see the paper by Kanarik et al 10 For GaN, the reported plasma assisted ALE relies-regarding the adsorption step-either on oxidation, using O 2 plasma 11,12 or H 2 O 2 solution, 13 or on chlorination of GaN surfaces to form GaCl x by-products. 14,15 For the activation step, the use of Ar ion bombardment enables a unidirectional reaction, which is required for patterned features. 14,15 In this work, we propose a comparative study of ALE processes for undoped, c-oriented, Ga-polar GaN, relying both on Cl 2 based plasma for the absorption step, but which are using two different rare gases for the activation step, namely, Ar and Kr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the ALE studies using plasmas have been investigated by adsorbing reactive gases such as radicals or reactive molecules on the surface for the modification of the surface by chemisorption, and then by removing the modified surface layer only by using energetic ions. Using these techniques, a precise etch depth/cycle of various semiconductor related materials such as Si, III‐V compounds, metals, and 2D materials has been achieved . As the plasma sources for radical adsorption, inductively coupled plasma (ICP) and capacitively coupled plasma (CCP) were mainly used while, as the desorption sources, an ion/neutral beam or conventional radio frequency (RF) biasing was used for anisotropic ALE technology.…”
Section: Introductionmentioning
confidence: 99%